Development of an indoor tracking system - Pang, Andy Teng Seng (2015)
Indoor localisation is an added feature in security industry, however using Satellite based Global Positioning System (GPS) to locate a subject in an indoor environment are very inaccurate due to signal attenuation, therefore other technologies are required. In this project, the ZigBee which uses Received Signal Strength Indicator (RSSI) based on 2.4GHz wireless communication to locate the subject. However due to high signal attenuation in an indoor environment, the RSSI gathered have to be processed before they could be used for fingerprinting. Data processing technique uses standard deviation to eliminate noises and averaging the data within acceptable range. Methods of fingerprinting location of the subject using trilateration and energy management such as automated room lighting are explored.